2021
DOI: 10.1001/jamaneurol.2021.2485
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital Comprehensive Stroke Center vs Primary Stroke Center Triage in Patients With Suspected Large Vessel Occlusion Stroke

Abstract: IMPORTANCE Endovascular therapy (EVT) improves functional outcomes in acute ischemic stroke (AIS) with large vessel occlusion (LVO). Whether implementation of a regional prehospital transport policy for comprehensive stroke center triage increases use of EVT is uncertain.OBJECTIVE To evaluate the association of a regional prehospital transport policy that directly triages patients with suspected LVO stroke to the nearest comprehensive stroke center with rates of EVT. DESIGN, SETTING, AND PARTICIPANTSThis retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Recently, implementation of a prehospital triage program for patients with suspected large vessel occlusions directly to appropriate endovascular-capable stroke centers significantly improved rates of endovascular therapy, which is known to improve functional outcomes. 40 Similarly, the use of mobile stroke units, even in smaller urban areas have shown to be effective in reducing door-to-needle time compared with traditional emergency transport. 41 , 42 High-risk patients, patients with DE, and minority patients should be intentionally targeted by such programs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, implementation of a prehospital triage program for patients with suspected large vessel occlusions directly to appropriate endovascular-capable stroke centers significantly improved rates of endovascular therapy, which is known to improve functional outcomes. 40 Similarly, the use of mobile stroke units, even in smaller urban areas have shown to be effective in reducing door-to-needle time compared with traditional emergency transport. 41 , 42 High-risk patients, patients with DE, and minority patients should be intentionally targeted by such programs.…”
Section: Discussionmentioning
confidence: 99%
“…This has led to reorganization in subspecialties within the clinical‐academic environment. To name a few: stroke centers have been established [1] to improve access to recanalization therapy; movement disorder clinics [2] and epilepsy units [3] now liaise with neurosurgery to offer surgical options on top of other medical approaches; and neuromuscular centers [4] offer multidisciplinary care including gene therapy. While this subspecialization is useful for the development of specific competences and for research, it presents the risk of silos and fragmentation [5] in the sense that each subspecialty works independently without a more comprehensive view of the condition of the individual patient.…”
Section: Introductionmentioning
confidence: 99%
“…In many geographic regions, the additional transport time to the EVT center may be less than 30 min, and the most recent American Heart Association (AHA) guidelines suggest direct transfer to CSCs for patients within 30 min of CSC in urban regions, 45 min for suburban, and 60 min for rural areas 8. In previous studies across a variety of geographic regions, direct field triage has been shown to increase rates of EVT9 and reduce time to treatment, but those studies were conducted over an approximately 2 year time span 10–12. The impact of triage on time to treatment over a longer time span is unknown.…”
Section: Introductionmentioning
confidence: 99%